2018
DOI: 10.1002/job.2282
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and employee engagement: The moderating role of CSR‐specific relative autonomy and individualism

Abstract: Summary Growing evidence suggests that employees' perceptions of their employer's corporate social responsibility (CSR) relate positively to employee work engagement. This is an important connection given the impact of work engagement on both employee health and organizational productivity, as well as the importance of CSR for society. In this paper, however, we argue that the CSR perceptions–work engagement relationship cannot be assumed to be universal and that both individual and contextual factors will pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 146 publications
5
134
1
3
Order By: Relevance
“…In this respect, stakeholders are more likely to consider such a company as legitimate and reward it, leading to improvement on its competitiveness. Stakeholders therefore like engaging with organizations that proactively contribute to creating meaningful benefits that enhance their lives (Flammer, ; Rupp et al, ; Singh & Agarwal, ). In summary an organization's CSR strategy, whether proactive or reactive, influences its CSR impacts on its competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this respect, stakeholders are more likely to consider such a company as legitimate and reward it, leading to improvement on its competitiveness. Stakeholders therefore like engaging with organizations that proactively contribute to creating meaningful benefits that enhance their lives (Flammer, ; Rupp et al, ; Singh & Agarwal, ). In summary an organization's CSR strategy, whether proactive or reactive, influences its CSR impacts on its competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate social responsibility (CSR) has been a field of interest over the past couple of decades. The challenges encountered in the form of rapidly evolving technology, frequently changing market conditions along with a matured well‐informed customer resulted in increasing the attention paid by companies towards their respective stakeholders along with the social, economic, and the environmental issues (Garavan & McGuire, ; Rupp et al, ). Employees within the organization are constantly inquiring about the meaning of the work done by them, and organizations failing to respond to these will encounter difficulties in retaining and obtaining the services of the most efficacious workers (Bhattacharya, Sen, & Korschun, ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that that offices with higher levels of corporate philanthropy would have higher average levels of employee attitudes. Rupp et al (2018) proposed that the relationship between CSR and EE is stronger among employees complying with, advocating for, and/or participating in CSR activities and that the amplification effect is stronger at the individual level of analysis. Their hypotheses were supported by data collected from a sample of 673 employees from Canada, China, France, Hong Kong, and Singapore.…”
Section: Literature Related To the Impact Of Csr On Eementioning
confidence: 99%